PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT PEGADAIAN (PERSERO) CABANG SRAGEN - prayogo aris munandar; Suprayitno Suprayitno; Sunarso Sunarso (Universitas Slamet Riyadi, 2022)
Facing the development of an increasingly rapid and technological era, utilizing technology is one of the most appropriate things for today. This research is a survey. This type of data uses qualitative data and quantitative data. Sources of data using primary data and secondary data. The population in this study is an unknown number of IndiHome customers in the city of Surakarta. The number of samples used in this study were 100 people. The sampling technique used was purposive sampling technique. Data collection techniques using questionnaires and literature study. Data analysis used descriptive analysis, multiple linear regression test, t test, F test, and coefficient of determination test. Partially, the results showed that price, service quality, product quality and brand image had a significant effect on customer satisfaction.